WAYS FOR PEACEFUL SOCIETY IN ISLAMIC LAW - Qadoos, Abdul; ??M?EK, Murat (IJISH (International Journal of Islamic Studies and Humanities), 2020)
Every individual is the first unit of the society. Family becomes by living the individuals together and then society becomes by the different family groups. The family happiness and prosperity is based on the individual while the society happiness and prosperity lies on the groups of family. Although the establishment of a peaceful society is essential for the prosperity of the country. It is a universal fact that no country can develop until and unless the existence of peace in any field. Peace is the foremost priority in the development of the country. That is why in the modern world, those countries that are in the race for development, in fact there is peace. Peace is the only way that can lead the people to a successful life, and this is the philosophy that Allah revealed to His Prophet Mohammed fourteen hundred years ago in the last book of the Holy Qur??n. Allah says. Translation: And (I grant a) peace in fear. Islam is a peaceful religion, its best examples, we can see, in the practical life of Holy Prophet (SAW). He was the Messenger of Allah (SWT) to convey the message of honesty, piousness, peace, mercy, integrity, and love. He had never done any activity which indicate act of terrorizing, misconduct, racism and violation against humanity. This study was aimed to analyze the basic and essential virtues of Islam for establishment of peaceful society in Islamic Law.